2011
DOI: 10.1016/j.nic.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Neurobrucellosis

Abstract: Brucellosis is a multisystem infection with a broad spectrum of clinical presentations. Its nervous system involvement is known as neurobrucellosis. Neurobrucellosis (NB) has neither a typical clinical picture nor specific cerebrospinal fluid (CSF) findings. Its diagnosis is based on the existence of a neurologic picture not explained by any other neurologic disease, evidenced by systemic brucellar infection and the presence of inflammatory alteration in CSF. Imaging findings of NB is divided into four categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 43 publications
1
40
0
15
Order By: Relevance
“…Myelitis, radiculoneuritis, brain and epidural abscess, and meningovascular syndromes are other inflammatory processes encountered [2]. MRI examination may present with normal findings, inflammatory changes, or white matter and vascular changes [8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…Myelitis, radiculoneuritis, brain and epidural abscess, and meningovascular syndromes are other inflammatory processes encountered [2]. MRI examination may present with normal findings, inflammatory changes, or white matter and vascular changes [8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…MRI with contrast is the method of imaging to evaluate neurobrucellosis. Kizilkilic and Calli [3] indicated that the course of cerebral parenchymal infection in neurobrucellosis resembles to those seen in chronic brain abscesses starting from early cerebritis to well demarcated rim enhancing abscess formation. At the presented case, brain MRI showed diffuse pachymeningeal thickening and enhancement together with nodular, diffusely enhancing, T2 hyperintense lesions located at the right frontal cortex.…”
Section: Discussionmentioning
confidence: 97%
“…Most common manifestations of neurobrucellosis are meningitis, meningoencephalitis, cerebritis, brain abscess, leukoencephalopathy, demyelinating or vascular diseases [3,4]. Among those, meningitis and meningoencephalitis are seen in approximately half of the cases [3]. Pseudotumor cerebri together with optic neuritis may cause papilledema.…”
Section: Discussionmentioning
confidence: 99%
“…The vestibulocochlear nerve has been reported to be the most commonly affected cranial nerve where the patients present with vestibuloacoustic neuritis or hearing loss [6]. …”
Section: Discussionmentioning
confidence: 99%